Log in to add a comment

Log in to add a comment

2y ^2 + 21 = 13y

2y^2 + 21 -13y

2y^2 - 13y + 21

multiply 2 with 21 we get 42

then the equation be y^2 - 13y + 42

let factorise we get

[( 2y - 7 ) ( 2y -6)]/ 2

[ (2y-7) 2( y-3) ]/2 taking 2 common outside and divide with 2

(2y-7) ( y -3) = o

2y =7 ; y =3

y = 7/2 and y = 3

if we were to substitute the values, then we would get:

the equation is 2y^2+21=13y right, so transpose to make a zero.

make it 2y^2-13y+21=0

this is in the form of ay^2+by+c=0, right?,

now, a=2, b=-13, c=21.

now, using the equation itself.

the equation is, y= [-b +/- √(b²-4ac)]÷2a.

so, y={-(-13)+/- √(-13²-4(2*21)}/4

this equals to {13+/-√(169-168) }/4

this is [13+/- 1] /4

so, this can either be [13+1]/4 or [13-1]/4

so the answers are 12/4 and 14/4, which are 3 and 3.5 respectively.